Liquid biopsy for non-invasive monitoring of patients with kidney transplants - Nassar, Anthony; Cashman, Katharine; Rao, Shreya; Dagher, Maribel; O’Brien, Connor; Afif, John; Cravedi, Paolo; Azzi, Jamil R. (Frontiers in Transplantation, 2023)
Purpose of review: The current tools for diagnosing and monitoring native kidney diseases as well as allograft rejection in transplant patients are suboptimal. Creatinine and proteinuria are non-specific and poorly sensitive markers of injury. Tissue biopsies are invasive and carry potential complications. In this article, we overview the different techniques of liquid biopsy and discuss their potentials to improve patients kidney health. Recent findings: Several diagnostic, predictive and prognostic biomarkers have been identified with the ability to detect and monitor the activity of native kidney diseases as well as early and chronic allograft rejection, like ddcfDNA, exosomes, mRNA/miRNA, proteomics etc. While results are encouraging, additional research is still needed as no biomarker appears to be perfect for a routine application in clinical practice. Summary: Despite promising advancements in biomarkers, the most important issue is the lack of standardized pre analytical criteria. Large validation studies and uniformed standard operating procedures are required to move the findings from bench to bedside. Establishing consortia like the Liquid Biopsy Consortium for Kidney Diseases can help expedite the research process, allow large studies to establish standardized procedures, and improve the management and outcomes of kidney diseases and of kidney transplant recipients.